The relationship between eating habits, socio-demographic characteristics and body mass index among undergraduate students from two selected universities, Tanzania - Msoga, Japhet J.; Anasel, Mackfallen (International Journal Of Community Medicine And Public Health, 2020)
Background: Obesity is a current public health concern for both developed and developing countries. Previous studies have demonstrated that, university students exhibit poor eating habits and gain body weight more rapidly than the general population. The aim of this study was to investigate how socio-demographic characteristics and eating habits relate to body mass index (BMI) among undergraduate students from two selected universities in Morogoro region, Tanzania. Methods: This cross-sectional study was conducted at Mzumbe University and Jordan University College. Simple and cluster random sampling were used to select 200 students from the two universities. Questionnaire and Anthropometric measurements were used during data collection. One-way ANOVA and multiple linear regressions analysis were deployed with an assistance of computer software called SPSS. Results: The findings showed that each additional healthy eating habit score was insignificantly associated with 0.043 units decrease in BMI (p>0.05). This study found significant associations between mean BMI and female gender, age and place of origin (p<0.05). The results showed that each additional year of age was significantly associated with 0.495 units increase in BMI and female respondents were having 2.168 higher BMI than males. In addition, respondents from rural had significant lower BMI by 1.59 as compared to their urban counterparts. Conclusions: The study concluded that age, gender and place of origin relate with undergraduate student’s BMI significantly. The study recommend that public health planners and implementers should target age, gender, place of origin as well as eating habit during fighting for obesity among undergraduate students.